Applying enterprise: active learning environments for business Higher National Diploma students. Issue 5 (4th July 2018) - Bell, Heather; Bell, Robin
Abstract: This article details an approach to teaching entrepreneurship to Higher National Diploma (HND) students that combines lecture-based and experiential learning processes to increase student learning, comprehension, and entrepreneurial skills. A UK university redesigned an entrepreneurship course to have students design and implement business plans for a pop-up shop and an event in the local community, while working closely with instructors and outside stakeholders. The lectures used in the lessons were designed to complement the enterprise activities and be immediately applied in group work settings. Data were collected from student reflections and analysed against instructor reflections to highlight both the success and challenges of this approach, as well as any areas of dissonance between student and instructor observations. While the benefits of active and experiential learning processes are highlighted in the literature, this article examines these teaching methods specifically in a HND context, an area in which research on the benefits of these teaching methods for developing entrepreneurial students and for developing students prepared for undergraduate education has been limited.